Non–Firearm-related Homicides at the Medical University of South Carolina, 2013–2018. (28th June 2022) - Sullivan, Christopher; Presnell, Susan Erin
Abstract: After high-profile events involving firearms, gun violence often becomes the center stage of public discourse with national media attention, overshadowing less common causes of homicidal deaths, such as sharp force injury, blunt trauma, and asphyxia. A retrospective analysis of all cases referred for medicolegal autopsy to the Medical and Forensic Autopsy Division of the Department of Pathology and Laboratory Medicine at the Medical University of South Carolina from 2013 to 2018 documented 793 deaths where the manner was classified as homicide. Of these, 18% (144) of the deaths were caused by non–firearm-inflicted injuries. Nonfirearm homicides were further categorized by method; demographic data including decedent age, race, and sex; and other variables such as incident site, decedent relationship status to the alleged perpetrator, number of other homicide fatalities associated with a homicide event, and the presence of drugs and alcohol in the decedents. Data accrued in this review were compared with national statistics published by the Centers for Disease Control and Prevention and to the overall Medical University of South Carolina firearm-related homicide decedent demographic statistics for this same period. Findings augment existing information available regarding non–gun-related homicides and may be valuable in contributing to the ongoing public and political debate regarding firearm and nonfirearm fatalities.